The challenges of urgent radical sigmoid colorectal cancer resection in a COVID-19 patient: A case report. (2020) - Huang, Zhengbin; Yan, Jijun; Jin, Tian; Huang, Xiufang; Zeng, Guoxiang; Adashek, Michael L.; Wang, Xinhai; Li, Jieping; Zhou, Dan; Wu, Zhengqi
Highlights: The first reported case of urgent exploratory colorectal surgery and sigmoid mass resection in a COVID-19 positive patient. Discussion of surgical techniques to minimize theoretical viral transmission pre, peri and postoperatively. Discussion or risks of fecal transmission of COVID-19 transmission intraoperatively. Discussion of personal protective equipment utilization and post-surgical COVID-19 screening among surgical healthcare staff. Abstract: Introduction: The COVID-19 pandemic presents a unique global health challenge further complicating surgical management of COVID-19 positive patients due to a lack of published literature. Case: Within we discuss a 48-year-old Chinese man, presenting with acute gastrointestinal obstruction due to sigmoid colonic mass. The patient was screened and tested positive for COVID 19 due to his employment in Wuhan, China at the COVID-19 pandemic epicenter. The patient was subsequently taken for open sigmoid colonic resection, however the case presented multiple challenges due to the patient's COVID-19 positive status. Discussion: The challenges of surgical management of COVID-19 positive patients exist are four-fold. First the unknown efficacy of pre-surgical risk stratification in COVID-19 positive patients, second the risk of aerosolized COVID-19 transmission during intubation for surgery, third the risk of fecal COVID-19 transmission to surgical staff during large bowel resection, and fourth the post-operative challenges of caring for COVID-19 positive patients. Conclusion: Further research is needed into these topics, as well as the medical management of COVID-19 surgical patients.